2020
DOI: 10.1371/journal.pone.0239285
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition behaviour of mated or unmated Cleruchoides noackae (Hymenoptera: Mymaridae)

Abstract: Cleruchoides noackae (Hymenoptera: Mymaridae), native to Australia, is the most promising biological control agent for Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae), an exotic Eucalyptus spp. pest in Brazil. The aim of this study was to determine the courtship behaviour, mating and oviposition of unmated or mated C. noackae females parasitizing T. peregrinus eggs utilizing the same rearing system used in biological control programmes in Brazil. The mating behaviour of eleven C. noackae unmated couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…These females bend their abdomen dorsally and spread their wings, preparing to copulate ( Romano et al 2016 , 2018 ). Cleruchoides noackae Lin & Huber (Hymenoptera: Mymaridae) mated shortly after emergence, without courtship or female receptivity for additional copulations ( Mutitu et al 2013 , Becchi et al 2020 ). Rejection of mating attempts is a common behavior among females, wherein they walk or fly away from the male ( Avila et al 2016 , Romano et al 2016 ), such as that observed for P. bliteus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These females bend their abdomen dorsally and spread their wings, preparing to copulate ( Romano et al 2016 , 2018 ). Cleruchoides noackae Lin & Huber (Hymenoptera: Mymaridae) mated shortly after emergence, without courtship or female receptivity for additional copulations ( Mutitu et al 2013 , Becchi et al 2020 ). Rejection of mating attempts is a common behavior among females, wherein they walk or fly away from the male ( Avila et al 2016 , Romano et al 2016 ), such as that observed for P. bliteus .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, mating period varies with species, with 2–50 s for Cl. noackae ( Mutitu et al 2013 , Becchi et al 2020 ) and 23.3 s for C. tarsalis ( Cheng et al 2004 ). Furthermore, P. bliteus males court virgin or mated females, similar to Anastatus disparis Ruschka (Hymenoptera: Eupelmidae) ( Liu and Hao 2019 , Liu et al 2020 ), whereas Co. urabae was attracted only by virgin females ( Avila et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…parvula , 18 and even characterized 18 microsatellite markers of S. empoascae 21 . The courtship, mating and oviposition behaviors of another mymarid wasp, Cleruchoides noackae also have been described in detail 22 . A new mymarid species, Anagrus rugmanjonesi Triapitsyn & Adachi‐Hagimori, sp.n., 23 that parasitized eggs of tea green leafhopper Empoasca onukii Matsuda in Japanese tea plantations, also has been described.…”
Section: Introductionmentioning
confidence: 99%